Optimising the flux barriers of interior permanent magnet machine for noise reduction under certain load conditions. Issue 11 (26th July 2021) - Ge, Haorui; Guo, Baocheng; Qiu, Xin; Yang, Jianfei; Feng, Chunmei; Bai, Chenguang; Jin, Zhen; Zhang, Yongmin
Abstract: This study proposes a method to reduce the electromagnetic noise of a double‐layer interior permanent magnet synchronous motor (DIPMSM) by optimising the flux barrier. First, a noise prediction model of the 36‐slot/8‐pole DIPMSM is established by finite element (FE). According to the simulation results, the noise of the motor is the loudest at 5000 rpm, especially with a noise component of 3333.3 Hz. From the results of modal analysis, it can be concluded that the four‐order radial force with a frequency of 3333.3 Hz resonates with the stator, resulting in the loudest noise. Then, the source of the radial force that causes the loudest noise is analysed, and it can be found that the 9th and 11th harmonics of rotor magnetic motive force have the greatest contribution to the force. By optimising the rotor, the radial force contributed by the 9th and 11th harmonics is weakened, thereby reducing the noise caused by these harmonics. Finally, the electromagnetic performance and noise of the optimised motor are checked by FE. Compared with the initial rotor, the torque ripple is reduced by 26.79%, and noise is reduced by 5.542 dB. The noise test on the prototype verifies the accuracy of the noise prediction model.